PENGEMBANGAN BAHAN AJAR ETNOMATEMATIKA DENGAN PENDEKATAN KONTEKSTUAL UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP NEGERI 2 PADANGSISIMPUAN - Harahap, Muhammad Syahril; Elindra, Rahmatika; Nasution, Zakiya Maimunah; Nasution, Nurhidaya Fithriyah; Nasution, Febriani Hastini (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2024)
Abstract This research aims to produce ethnomathematics teaching materials with a contextual approach to improve the mathematical communication skills of students at SMP Negeri 2 Padangsidimpuan and determine the quality of teaching materials in terms of validity, practicality and effectiveness. This research is Research and Development (R&D) research with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The subjects in this research were 29 students in class VIII-3 of SMP Negeri 2 Padangsidimpuan. Data collection techniques in this research are questionnaires, tests and documentation. The instruments used include 1) a questionnaire sheet in the form of a validation questionnaire by experts to see the validity of the product and a student response questionnaire to see the practicality of the product and 2) a test sheet for the effectiveness of the product being developed. Validation was carried out by media experts, material experts, language experts and cultural experts who then carried out product trials by looking at responses to product use and student test results based on mathematical communication skills. Based on the results of this research, product validity was obtained with an average percentage of 84.075% in the